CYAN generating agricultural capacity through a research and development hub for climate-smart and urban agriculture - Bello, Ella Rose M.; Simoun T. Ong (Quezon City College of Architecture, University of the Philippines Diliman, 2025)
A major environmental shift's indisputable effects have led to a necessary switch in agricultural prioritization. The phenomenon of urban sprawl, plus the repercussions of climate change, significantly burdens the agrarian sector's competitiveness in providing continuous support. A drop in agricultural productivity is claimed to result from the rapid merging of the rural and urban areas, where the forefront of these expansions is the lands intended for agriculture. Income decline as collateral of climate emergencies has driven farmers out of agriculture. Burdened by the lack of prioritization towards enhancing agricultural capacity, these long-standing issues highlight the need for a holistic approach to acclimate current farming technologies to address these effects. In response, an agricultural research and development hub that intends to cultivate spaces for innovation in crop and aquaculture research to reach climate-smart agriculture standards while enhancing urban agricultural resolves the initial issue. By incorporating an aquaponic demo form farm, a modern agricultural technology developed through research and development, into the hub as a promotional tool for the future of agriculture, the issue of decreased patronization towards agriculture is simultaneously addressed. Through a qualitative research approach, this comprehensive design project inquiries into standard considerations in the design of a research and development hub centered on agricultural research and modern farming methods.
Include appendices
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Urban agriculture; Aquaponics